Application of MCDM methods in short-term planning for private universities based on balanced scorecard: a case study from Iran. (1st January 2012) - Hashemkhani Zolfani, Sarfaraz; Safaei Ghadikolaei, Abdolhamid
It is almost 20 years since, private universities are being regulated by The Ministry of Science, Research and Technology and nowadays, there are many universities and institute working in higher education in Iran. The aim of this research is to help universities with short-term planning. This research applies two multiple criteria decision-making methods in a comparison way. Decision-making trial and evaluation laboratory (DEMATEL) and analytic network process (ANP) both were applied separately to BSC and the results of the both methods were used. In this research DEMATEL and ANP were used in each perspective of BSC to identify an important index in each perspective. Finally, authors believed that results of DEMATEL are of great importance, because it is based on the cause and effects relation between indices and helpful to minimise the risk. The results of the ANP method may be applied as these universities' main concern is to decrease the risk along with a short-term planning to improve their positions in a competitive environment.